IMPROVING THE TREATMENT OF DENTAL CARIES IN SCHOOL-AGE CHILDREN USING THE REMINERALIZATION METHOD - Dinikulov J. A.; Abdukayumova Z. X. (Scholars Digest Publishing, 2025)
Despite advances and innovations in the field of dentistry, the issue of dental caries remains highly relevant in pediatric dentistry. As a result, not only do complications arise in the oral cavity, but diseases in other organ systems, psychological problems, and significant delays in growth and development can also occur. Premature loss of permanent teeth can lead to occlusal defects, which in turn cause issues with digestion, speech, and aesthetics. This highlights the importance of treating caries at an early stage — specifically during the initial "white spot" phase — to prevent future tooth loss and its associated complications.
Keywords: Caries, demineralization, remineralization.